Student Responses to the Policy of KPID West Java Regarding Religious Programs in Television - Manap, Manap Solihat; Melly, Melly Maulin P.; Calista, Calista Azzahra (UPT Publikasi Ilmiah UNISBA, 2023)
The study aimed to explain and analyze Student Responses to Policy Circular Number 1 of 2022 KPID West Java concerning Religious Programs in Television. Policy Circular containing guidelines for radio and television broadcasting institutions in West Java regarding how religious broadcasts should be carried out. This research uses a qualitative approach with a case study method with a single case. Primary data were obtained from in-depth and focused interviews with informants, field observations in the form of notes about situations and events, and informant data. Researchers selected all informants in this study using purposive and snowball sampling techniques. College students are aware of the circular letter through the West Java KPID website and social media, watch religious broadcasts that offend other religions, appreciate this circular letter, and hope that the quality of religious broadcasts will increase and support national integration. College students participate actively by criticizing religious issues, being responsive in reporting violations of religious programs, and educating those closest to them about broadcasting policies. The research conclusion is that West Java KPID Circular Letter Number 1 of 2022 is relevant in overcoming broadcasting problems developing in West Java. KPID is responsive in its efforts to create inter-religious harmony and national integration through its policies.